Sharia Compliance and Trust: Online Purchase Intentions of Generation Z in E-Commerce - Nur Faizah; Mitra Riani Aisyah (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2023)
Numerous factors drive individuals to engage in online shopping, including considerations such as affordability, product quality, variety, trustworthiness, convenience, and various other elements. In this study, four independent variables—namely, Sharia Compliance (X1), trust (X2), usability (X3), and trend (X4)—are utilized, with online purchase decisions serving as the dependent variable (Y). The primary aim of this research is to assess and dissect the influence of Sharia Compliance, Trust, Usability, and Trend on online purchase decisions within the Generation Z demographic in the Gorontalo Province. Employing a quantitative approach, this study involves data collection from 100 respondents through the use of questionnaires. The statistical tool of choice is multiple linear regression analysis. The results of partial testing reveal that while Sharia Compliance exerts a positive influence, its impact on online purchase decisions lacks statistical significance. Conversely, trust, usability, and trend exhibit both positive and statistically significant effects on online purchase decisions. Nevertheless, when considered collectively in a simultaneous examination, Sharia Compliance, trust, usability, and trend collectively demonstrate a positive and statistically significant impact on online purchase decisions among Generation Z individuals in the Gorontalo Province